Composition of Flavan-3-ol Monomers in Mature Cabernet Sauvignon Fruit at Different Grapevine Age in Yantai, China - Zhao, Xinjie; Deng, Bo; Mu, Jingxia; Li, Chunguang; Wu, Feng; Han, Ning; Zhao, Yueling (Asian Journal of Chemistry, 2013)
We have identified the phenols, tannins and the primary flavan-3-ol monomers including (+)-catechin, (-)-epicatechin, (+)-gallocatechin grade, (-)-epigallocatechin, (-)-catechin gallate, (-)-epicatechin, gallocatechin gallate and (-)-epigallocatechin gallate in different tissues (flesh, peduncle, skin and seed) of 5 year and 10 year grapevines grape (Cabernet sauvignon) and quantified their content by high performance liquid chromatography. The results show that there were significant differences in the concentration of phenols, tannins and the primary flavan-3-ol monomers among different tissues and grapevine age. Especially, the concentrations of flavan-3-ol monomers were higher in all four grape tissues of 10 year grapevines grape than those of 5 year one. In terms of (-)-catechin gallate, it was detected only in 10 year grapevines grape berry and the flesh of 5-year grapevines grape. The concentrations of (+)-catechin and (-)-epicatechin in the seeds of 10-year grapevines grape were about twice as much as those in 5 year ones.